A New Technique for Reconstruction of Medium-Sized Eyelid Defects (A Modification of Tessier Nasojugal Flap) - Yousefiazar, Awat; Hassanzadazar, Mohsen (Facial Plastic Surgery, 2018)
Eyelid reconstructions are considered challenging surgical procedures, which are mostly performed due to trauma, tumor resections, and congenital defects. Several techniques can be used to reconstruct the lower eyelid defects. In this study, the authors aimed to introduce a new single-step technique for the reconstruction of medium-sized lower eyelid defects while preventing ectropion. A modified nasojugal flap was designed and harvested after making a complete incision. A dermal extension from the nasolabial area was added to the end of the nasojugal flap. A tunnel was created under the orbicularis oculi muscle, and the dermal tail was passed through this tunnel toward the lateral canthus. The flap was fixed in its new position by suturing. The defect in the nasojugal area was repaired by bilateral advancement of the surrounding tissue. The recovery of the patients was followed up for 6 months, which included assessment of the eyelid position and donor site morbidity. A total of four patients with an age range of 64 ± 8 years who suffered from basal cell carcinoma were treated using the technique introduced in this study. No ectropion or abnormal eyelid position nor donor site morbidity was observed during the follow-up period. Reconstruction of a medium-sized lower eyelid defect using nasolabial flap with local modification combined with orbital canthus fixation resulted in appropriate functional and cosmetic outcomes and limited the risk of complications and morbidity.
Keywords: lower eyelid reconstruction; nasolabial flap; nasojugal flap; ectropion